Preparation and application of new flower-shaped composite flame retardant based on Co / Cu-MOF

By adopting a new flower-like composite flame retardant based on Co/Cu-MOF, the problem of degradation of mechanical properties caused by the addition of flame retardant in polyurea materials is solved, and the effect of significantly improving flame retardant performance without affecting the mechanical properties is achieved, and a polyurea material with rapid curing and excellent fire retardant performance is provided.

CN116606447BActive Publication Date: 2025-04-25QINGDAO UNIV OF TECH

Patent Information

Application Number
CN202310580886.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-23
Publication Date
2025-04-25
Estimated Expiration
2043-05-23

Smart Images

  • Figure CN116606447B_ABST
    Figure CN116606447B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation and application of a novel flower-shaped composite flame retardant based on Co / Cu-MOF for polyurea materials. The novel flower-shaped composite flame retardant based on Co / Cu-MOF first prepares a cubic Co / Cu-MOF, then self-assembles a flower-shaped Co / Cu-MOF-ZIF by linking a coordination bond between Co metal ions and 2-methylimidazole ligands, and finally further forms a layered structure by introducing Ni ions and Fe ions to obtain the final product Co / Cu-MOF-ZIF-LDH flame retardant. The present invention also provides a polyurea material with excellent flame retardant properties, and the addition amount of the novel flower-shaped composite flame retardant in the polyurea material is 0.5-6.0wt%. By adding the novel flower-shaped composite flame retardant, the flame retardant properties of the polyurea material are improved without affecting the mechanical properties of the polyurea material, which has important social significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic polymer flame retardants, relates to a flame retardant for reactive polyurea, and specifically relates to the preparation and application of a novel flower-shaped composite flame retardant based on Co / Cu-MOF. Background Art

[0002] Polyurea is an elastomeric material generated by the reaction of isocyanate and amino compounds. It has excellent mechanical properties, is insensitive to environmental humidity, and has excellent corrosion resistance. It is widely used in many fields such as concrete protection, steel structure anti-corrosion, and roof waterproofing. However, polyurea is a flammable polymer material and has certain safety hazards during use. To solve this problem, it is necessary to add flame retardant ingredients to the polyurea material.

[0003] In the prior art, common flame retardants are mainly halogen flame retardants, phosphorus flame retardants and nitrogen flame retardants. Among them, halogen flame retardants have good flame retardant effects, but they are prone to produce a large amount of smoke and toxic gases during combustion, so they have been gradually eliminated. The organic phosphorus system in phosphorus flame retardants can play a dual role of flame retardant plasticizer, but it will produce some corrosive gases. Nitrogen flame retardants mainly play a flame retardant role by generating flame-retardant gases to dilute combustible gases and decompose themselves to absorb heat. Its biggest advantage is that it is colorless, halogen-free, and has no corrosive gases, which is very friendly to the environment. However, if nitrogen flame retardants are added to polyurea alone, as the amount added increases, although the flame retardant properties can be improved, it will also be accompanied by a decrease in mechanical properties. Invention patent application 201711385243.1 discloses "a halogen-free flame retardant and a flame-retardant polyurea elastomer coating". The flame retardant forms a carbonized layer after combustion to prevent the substrate from continuing to burn, and also has the characteristics of good thermal stability and low smoke generation; however, in the polyurea elastomer coating, the flame retardant is added in an amount of 10-30 parts, which is relatively large, thereby causing a certain impact on the mechanical properties of the polyurea.

[0004] Transition metal oxides have been widely studied for their excellent catalytic oxidation performance, and they also have good flame retardant effects. This is because transition metal oxides are good carbon formers and carbon catalysts. They can form carbon on the surface of polymers during thermal cracking and combustion of polymers, thereby isolating air heat and flames, and can also play a role in smoke suppression. However, there are still problems with the compatibility of inorganic nanoparticles with polymer matrices. Metal-organic frameworks (MOFs) have a certain solid structure that can produce permanent and stable pores, and these pores have adjustable and controllable properties. On the one hand, transition metal elements with good flame retardant effects can fit the metal nodes of MOFs. On the other hand, organic ligands, another important component of MOFs, can provide some flame retardant elements and groups, and can also enhance the compatibility with the polymer matrix, which can effectively solve the compatibility problem of inorganic nanomaterials added to polyurea as flame retardants.

[0005] Based on this, the researchers directly mixed some of the original MOFs into the polymer matrix and found that the MOFs material has certain flame retardant properties, but the effect is limited. This is because the structure of a single original MOF is relatively simple, and the metal site as a transition metal element can be catalyzed into carbon during the combustion process, and some types of ligands will generate non-flammable gases to reduce the concentration of combustible gases. At the same time, if the amount of flame retardant added is too high, it will often cause a significant decrease in the mechanical properties of the polymer material. How to solve the above problems while improving flame retardant properties is a topic facing researchers. Summary of the invention

[0006] In view of the problems existing in the MOFs flame retardant of polyurea materials in the prior art, the present invention provides a preparation and application of a novel flower-shaped composite flame retardant based on Co / Cu-MOF for polyurea materials. By adding the novel flower-shaped composite flame retardant, the flame retardant properties of the polyurea material are improved without affecting the mechanical properties of the polyurea material, which has important social significance.

[0007] The technical solution of the present invention is: a novel flower-shaped composite flame retardant based on Co / Cu-MOF, which is prepared by the following steps and methods:

[0008] (1) Preparation of Co / Cu-MOF: Copper nitrate trihydrate, cobalt nitrate hexahydrate and 1,4-terephthalic acid are dispersed in DMF solution, stirred magnetically at 400-600 rpm for 20-30 min until completely dissolved, acetonitrile solution is added and stirred continuously until uniformly mixed; then transferred to an autoclave for solvothermal reaction, cooled to room temperature after the reaction is completed, centrifuged, washed and dried to obtain the product Co / Cu-MOF. The weight ratio of copper nitrate trihydrate, cobalt nitrate hexahydrate and 1,4-terephthalic acid is 1:(4-6):(8-10); the specific conditions of the solvothermal reaction are reaction at 110℃~130℃ for 12-24h; and drying conditions are drying at 60-80℃ for 6-8h. The concentration of the DMF solution is 700-800g / L, and the concentration of the acetonitrile solution is 700-750g / L. The washing uses DMF solution and methanol solution in sequence, with concentrations of 700-800 g / L and 300-400 g / L respectively.

[0009] The Co / Cu-MOF is a cubic structure composed of lamellar structures containing cobalt elements, which has a relatively regular shape and a size of mostly 2-4 μm. The gaps between the lamellar structures vary greatly. The purpose of this step is to introduce Co ions into Cu-MOF, thereby achieving a change in the morphology in the next step of ZIF preparation, thereby improving the flame retardant effect of the flame retardant. If Co is not introduced into Cu-MOF in the form of ions in this step, the ZIF prepared in step (2) will not change in morphology.

[0010] (2) Preparation of Co / Cu-MOF-ZIF: The Co / Cu-MOF prepared in step (1) is dispersed in a methanol solution to obtain a dispersion system A, and 2-methylimidazole is dispersed in a methanol solution to obtain a solution B. Dispersion system A is dissolved in solution B and mixed, and ultrasonic dispersion is performed for 10 to 20 minutes; the weight ratio of the Co / Cu-MOF and 2-methylimidazole is 1:2 to 1:4. After centrifugal dispersion, washing and drying, the product Co / Cu-MOF-ZIF is obtained; the drying condition is 60-80°C and dried for 8-10 hours. The concentration of the methanol solution is 300 to 400 g / L. The washing is carried out using a methanol solution and an ethanol solution in sequence, with concentrations of 300 to 400 g / L and 400 to 500 g / L, respectively.

[0011] In this step, the Co metal ions and the 2-methylimidazole ligands are self-assembled into a three-dimensional framework structure through coordination bond linkage. The Co / Cu-MOF-ZIF prepared in this step has a significant change in morphology compared with the Co / Cu-MOF prepared in step (1), from a cubic structure to a flower-like structure, the petals of which are 2μm sheets, and the surface is relatively smooth. Based on the change from the cubic structure to the flower-like structure, the Co / Cu-MOF-ZIF prepared in step (2) has a complex channel, which is conducive to the tortuosity effect. In addition, the flower-like structure has a larger area of ​​barrier effect and a larger specific surface area, which is also conducive to more active sites playing a catalytic role in the combustion process, thereby achieving a significant improvement in flame retardant properties.

[0012] (3) Preparation of Co / Cu-MOF-ZIF-LDH: Disperse the Co / Cu-MOF-ZIF, nickel nitrate hexahydrate and ferric nitrate nonahydrate prepared in step (2) in an ethanol solution, and stir magnetically at 300-500 rpm for 5-6 hours; centrifugal dispersion, washing, and freeze drying are performed to obtain the final product Co / Cu-MOF-ZIF-LDH, i.e., the novel flower-shaped composite flame retardant. Wherein, the weight ratio of the Co / Cu-MOF-ZIF, nickel nitrate hexahydrate and ferric nitrate nonahydrate is (15-20):(6-8):1; the freeze drying condition is -50--60°C drying for 10-12 hours. The washing is carried out using anhydrous ethanol and water in sequence. The novel flower-shaped composite flame retardant prepared in this application can not only improve the fire safety performance of the polyurea material, but also does not affect the mechanical properties of the polyurea material.

[0013] In this step, the synthesized ZIF is used as a precursor, and a layered structure is further formed by introducing Ni ions and Fe ions. Compared with the Co / Cu-MOF-ZIF prepared in step (2), the Co / Cu-MOF-ZIF-LDH flame retardant obtained in this step has a change in the overall flower-like structure, some petals are gathered together, and the surface is no longer smooth. In addition, the petals present a thicker layer, and the center agglomeration is more obvious. Although the channel of the final product is slightly reduced compared with the Co / Cu-MOF-ZIF prepared in step (2), the barrier effect brought by the petals is significantly improved, so that the flame retardant performance is further improved.

[0014] As described above, the application of the new flower-shaped composite flame retardant is used to prepare a polyurea material with excellent flame retardant properties; the specific method is: adding the new flower-shaped composite flame retardant to a mixture of an amino-terminated polyether and an amine chain extender, and uniformly dispersing it by ultrasonication; then adding an isocyanate prepolymer to the system for reaction, and a polyurea material with excellent flame retardant properties can be obtained. Wherein, the addition amount of the new flower-shaped composite flame retardant is 0.5-6.0wt%. The new flower-shaped composite flame retardant is soaked in an acetone solution for 2-3 hours before being added to the mixture, in order to make the flame retardant uniformly dispersed in the mixture of the amine chain extender and the amino-terminated polyether, thereby ensuring the uniformity of the polyurea material.

[0015] The weight ratio of the amino-terminated polyether to the amine chain extender is 3:1-5:1; the volume ratio of the isocyanate prepolymer to the total of the amino-terminated polyether and the chain extender is 1:1-1:1.1; the isocyanate prepolymer is synthesized by prepolymerization of isocyanate and hydroxyl-terminated polyether in a weight ratio of 7:6-5:4 under N2 atmosphere. Compared with the prior art, the polyurea material used in this application not only achieves rapid curing of the polyurea material through the optimization of the formula, but also has considerable mechanical strength.

[0016] The isocyanate is 1,6-hexanediisocyanate (HDI), 2,2,4-trimethylhexanediisocyanate (TMHDI), isophorone diisocyanate (IPDI), tetramethyl meta-xylylene diisocyanate (TMXDI), toluene diisocyanate (TDI), dicyclohexylmethane diisocyanate (HMDI), 4,4'-diphenylmethane diisocyanate (4,4'-MDI) or 2,4'-diphenylmethane diisocyanate (2,4'-MDI); the amino-terminated polyether is polytetramethylene ether glycol di-p-aminobenzoate, amino-terminated polyoxypropylene ether, amino-terminated polyethylene glycol ether, amino-terminated polypropylene glycol ether, One or more of aminopolyglycerol ether and terminal amino pentaerythritol ether; the amine chain extender is one or more of diethyltoluenediamine, dimethylthiotoluenediamine, 4,4'-bis-sec-butylaminodiphenylmethane, 2,4-diamino-3,5-dimethylthiochlorobenzene, 2,4-diamino-3-methylthio-5-propyltoluene, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, 4,4'-bis-sec-butylaminodicyclohexylmethane, 3,3'-dimethyl-4,4'-bis-sec-butylamino-dicyclohexylmethane, low molecular weight polyoxypropylenediamine, N,N'-dialkylmethyldiamine and 3,3'-dichloro-4,4'-diaminodiphenylmethane. The terminal hydroxyl polyether is one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol and polybutylene glycol.

[0017] The polyurea material has excellent flame retardant performance. The polyurea material is prepared by the above method. The addition amount of the novel flower-shaped composite flame retardant in the polyurea material is 0.5-6.0wt%.

[0018] Flame retardant mechanism:

[0019] First, from the perspective of the gas phase mechanism, since the combustion of the polyurea material begins, the non-combustible gases such as NH3, N2 and H2O released by the combustion of MOF and LDH in the flame retardant dilute the concentration of combustible gases in the combustion part of the matrix and improve the necessary combustion conditions; at the same time, H2O will take away a large amount of heat to lower the temperature and inhibit combustion.

[0020] Secondly, in terms of the condensed phase mechanism, since the new flower-like composite flame retardant Co / Cu-MOF-ZIF-LDH contains a variety of transition metal elements, a variety of corresponding transition metal oxides, such as copper oxide and iron oxide, will be generated on the surface of the matrix as it ignites. Since these mixed metal oxides are alkaline substances, they have large specific surface area and porosity, as well as the characteristics of having many surface active centers, and can adsorb harmful acidic gases generated during the combustion of polymers.

[0021] Third, transition metal oxides are excellent catalysts that promote the formation of high-quality carbon layers. Therefore, by adding the transition metal-rich Co / Cu-MOF-ZIF-LDH new flower-shaped polyurea flame retardant, on the one hand, the transition metal oxides such as CuO and Fe2O3 generated can promote the formation of residual carbon more quickly, and on the other hand, the density and strength of the residual carbon are also improved, thereby enhancing the physical barrier. Its flower-like structure can increase the specific surface area, has more active sites, and can have a better catalytic effect. As the top priority of condensed phase flame retardancy, residual carbon can, on the one hand, act as a barrier to block the release of heat and smoke from the burning part; on the other hand, it can block the combustible gas and heat on the upper part of the burning matrix from further invading the interior of the matrix.

[0022] Beneficial effects of the present invention:

[0023] (1) The present application provides the preparation and application of a new flower-shaped composite flame retardant based on Co / Cu-MOF for polyurea materials. By adding the new flower-shaped composite flame retardant, the flame retardant properties of the polyurea material are improved without affecting the mechanical properties of the polyurea material, thereby solving the problems existing in the prior art.

[0024] (2) The novel flower-shaped composite flame retardant based on Co / Cu-MOF described in the present application has a convenient synthesis and preparation process, requires simple conditions, is green and environmentally friendly, and can provide a certain basis for the wider application of polyurea.

[0025] (3) The polyurea material using the aforementioned flame retardant not only achieves a significant improvement in fire resistance due to the optimization of the formula, but also achieves rapid curing of the material, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Attached Figure 1 These are the XRD patterns of the products of each step in the preparation process of the flower-shaped composite flame retardant in Example 1: Co / Cu-MOF (a), Co / Cu-MOF-ZIF (b) and Co / Cu-MOF-ZIF-LDH (c).

[0027] Attached Figure 2 These are SEM images of the products of each step in the preparation process of the flower-shaped composite flame retardant in Example 1: Co / Cu-MOF (a), Co / Cu-MOF-ZIF (b) and Co / Cu-MOF-ZIF-LDH (c).

[0028] Attached Figure 3 This is the XPS spectrum of the flower-shaped composite flame retardant Co / Cu-MOF-ZIF-LDH prepared in Example 1: full spectrum (a), N 1s (b), Cu 2p (c), Ni 2p (d), Co 2p (e) and Fe 2p (f) peak diagrams.

[0029] Attached Figure 4 The heat release rate curve of the polyurea composite material prepared in Example 3 is plotted against time.

[0030] Attached Figure 5 The CO yield of the polyurea composite material prepared in Example 3 is plotted against time.

[0031] Attached Figure 6 This is a flow chart for the preparation of the novel flower-shaped composite flame retardant described in this application. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with the embodiments.

[0033] Example 1: Preparation of novel flower-shaped composite flame retardant and flame-retardant polyurea composite material

[0034] (1) Preparation of Co / Cu-MOF cubic structure:

[0035] Disperse copper nitrate trihydrate, cobalt nitrate hexahydrate and 1,4-terephthalic acid in a (DMF) solution, stir magnetically until uniformly dispersed; add acetonitrile to the above solution after stirring until completely dissolved and continue stirring; move into a high-pressure reactor for solvent thermal reaction after stirring; cool to room temperature after the reaction is completed, then centrifuge and redisperse and wash with DMF and methanol solution, and finally dry to obtain the product Co / Cu-MOF. Wherein, the mass concentration of the DMF solution is 700g / L; the weight ratio of the copper nitrate trihydrate, cobalt nitrate hexahydrate and 1,4-terephthalic acid is 1:4:8; the speed of the magnetic stirring is 400rpm, and the stirring time is 20min; the solvent thermal reaction is 110℃, and the reaction time is 12h; the mass concentrations of the DMF and methanol solutions used for centrifugal washing are 700g / L and 300g / L respectively; the temperature of the dried sample is 60℃, and the drying time is 6h.

[0036] (2) Preparation of Co / Cu-MOF-ZIF: Co / Cu-MOF is dispersed in a methanol solution and recorded as dispersion system A, and 2-methylimidazole (2-M) is dispersed in another methanol solution and recorded as solution B; then solution B is quickly poured into dispersion system A, and after dispersion system A and solution B are completely mixed, the mixed solution is subjected to ultrasound; then methanol and ethanol are used for redispersion and washing by centrifugation, and finally the centrifuged product is collected and dried to obtain the sample Co / Cu-MOF-ZIF. Among them, the mass concentration of the methanol solution is 300g / L; the weight ratio of the Co / Cu-MOF and 2-M is 1:2; the ultrasound duration is 10 minutes in a beaker; the mass concentrations of the methanol and ethanol solutions used for the centrifugal washing are 300g / L and 400g / L respectively; the temperature of the dried sample is 60°C, and the drying time is 8h.

[0037] (3) Preparation of Co / Cu-MOF-ZIF-LDH: Co / Cu-MOF-ZIF, nickel nitrate hexahydrate and ferric nitrate nonahydrate are dispersed in an ethanol solution and continuously stirred by magnetic stirring; then, anhydrous ethanol and deionized water are centrifuged for redispersion and washing, and finally, the final product, i.e., a novel flower-shaped composite flame retardant, is obtained by drying. The mass concentration of the ethanol solution is 400 g / L; the weight ratio of the Co / Cu-MOF-ZIF, nickel nitrate hexahydrate and ferric nitrate nonahydrate is 15:6:1; the speed of the magnetic stirring is 300 rpm, and the stirring time is 5 h; the temperature condition of the freeze drying is -50 ° C, and the drying time is 12 h.

[0038] The Co / Cu-MOF-ZIF-LDH flame retardant prepared above is added to the polyurea B component to obtain a flame retardant polyurea composite material with excellent performance. The specific preparation method is: add the Co / Cu-MOF-ZIF-LDH flame retardant to a mixture of an amine chain extender and an amino-terminated polyether, ultrasonically and accompanied by stirring until uniform dispersion, and then add an isocyanate prepolymer to the mixture for reaction to obtain a polyurea material with excellent flame retardant properties. Wherein, the addition amount of the flame retardant is 0.5wt%. The weight ratio of the amine chain extender to the amino-terminated polyether is 1:3; the volume ratio of the isocyanate prepolymer to the sum of the amine chain extender and the amino-terminated polyether is 1:1. Among them, the amino-terminated polyether is polytetramethylene ether glycol di-p-aminobenzoate; the amine chain extender is dimethylthiotoluene diamine; the isocyanate is 2,4'-diphenylmethane diisocyanate (2,4'-MDI), and the hydroxy-terminated polyether is polyethylene glycol; the weight ratio of the isocyanate to the hydroxy-terminated polyether is 7:6.

[0039] Example 2: Preparation of novel flower-shaped composite flame retardant and flame-retardant polyurea composite material

[0040] (1) Preparation of Co / Cu-MOF cubic structure:

[0041] Disperse copper nitrate trihydrate, cobalt nitrate hexahydrate and 1,4-terephthalic acid in a (DMF) solution, stir magnetically until uniformly dispersed; add acetonitrile to the above solution after stirring until completely dissolved and continue stirring; move into a high-pressure reactor for solvent thermal reaction after stirring; cool to room temperature after the reaction is completed, then centrifuge and redisperse and wash with DMF and methanol solution, and finally dry to obtain the product Co / Cu-MOF. Wherein, the mass concentration of the DMF solution is 730g / L; the weight ratios of the copper nitrate trihydrate, cobalt nitrate hexahydrate and 1,4-terephthalic acid in DMF are 1:5:9 respectively; the speed of the magnetic stirring is 450rpm, and the stirring time is 25min; the solvent thermal reaction is 120℃, and the reaction time is 16h; the mass concentrations of the DMF and methanol solutions used for centrifugal washing are 700g / L and 300g / L respectively; the temperature of the dried sample preparation is 70℃, and the drying time is 7h.

[0042] (2) Preparation of Co / Cu-MOF-ZIF: Co / Cu-MOF is dispersed in a methanol solution and recorded as dispersion system A, and 2-methylimidazole (2-M) is dispersed in another methanol solution and recorded as solution B; then solution B is quickly poured into dispersion system A, and after dispersion system A and solution B are completely mixed, the mixed solution is subjected to ultrasound; then methanol and ethanol are used for redispersion and washing by centrifugation, and finally the centrifuged product is collected and dried to obtain the sample Co / Cu-MOF-ZIF. Among them, the mass concentration of the methanol solution is 350g / L; the weight ratio of Co / Cu-MOF and 2-M in the methanol solution is 1:3 respectively; the ultrasound duration is 15min in a beaker; the mass concentrations of the methanol and ethanol solutions used for the centrifugal washing are 300g / L and 400g / L respectively; the temperature of the dried sample is 70℃, and the drying time is 9h.

[0043] (3) Preparation of Co / Cu-MOF-ZIF-LDH: Co / Cu-MOF-ZIF, nickel nitrate hexahydrate and ferric nitrate nonahydrate were dispersed in an ethanol solution and stirred continuously by magnetic stirring; then, anhydrous ethanol and deionized water were centrifuged for redispersion and washing, and finally, the final product, i.e., a novel flower-shaped composite flame retardant, was obtained by drying. The mass concentration of the ethanol solution was 450 g / L; the weight ratios of Co / Cu-MOF-ZIF, nickel nitrate hexahydrate and ferric nitrate nonahydrate in the ethanol solution were 18:7:1, respectively; the speed of the magnetic stirring was 350 rpm, and the stirring time was 5.5 h; the temperature condition of the freeze drying was -55 °C, and the drying time was 10 h.

[0044] The Co / Cu-MOF-ZIF-LDH flame retardant prepared above is added to the polyurea B component to obtain a flame retardant polyurea composite material with excellent performance. The specific preparation method is: add the Co / Cu-MOF-ZIF-LDH flame retardant to a mixture of an amine chain extender and an amino-terminated polyether, ultrasonicate and stir until uniformly dispersed, and then add an isocyanate prepolymer to the mixture for reaction to obtain a polyurea material with excellent flame retardant properties. Wherein, the addition amount of the flame retardant is 3.0wt%. The weight ratio of the amine chain extender to the amino-terminated polyether is 1:4; the volume ratio of the isocyanate to the sum of the amine chain extender and the amino-terminated polyether is 1:1.05. Among them, the terminal amino polyether is terminal amino polyoxypropylene ether and terminal amino polyethylene glycol ether; the amine chain extender is N,N'-dialkyl methyl diamine; the isocyanate is 4,4'-diphenylmethane diisocyanate (4,4'-MDI), and the terminal hydroxyl polyether is polypropylene glycol; the weight ratio of the isocyanate to the terminal hydroxyl polyether is 6:5.

[0045] Example 3: Preparation of novel flower-shaped composite flame retardant and flame-retardant polyurea composite material

[0046] (1) Preparation of Co / Cu-MOF cubic structure:

[0047] Disperse copper nitrate trihydrate, cobalt nitrate hexahydrate and 1,4-terephthalic acid in a (DMF) solution, stir magnetically until uniformly dispersed; add acetonitrile to the above solution after stirring until completely dissolved and continue stirring; move into a high-pressure reactor for solvothermal reaction after stirring; cool to room temperature after the reaction is completed, then centrifuge and redisperse and wash with DMF and methanol solution, and finally dry to obtain the product Co / Cu-MOF. Wherein, the mass concentration of the DMF solution is 800g / L; the weight ratio of the copper nitrate trihydrate, cobalt nitrate hexahydrate and 1,4-terephthalic acid in DMF is 1:6:10 respectively; the speed of the magnetic stirring is 500rpm, and the stirring time is 30min; the solvothermal reaction is 130℃, and the reaction time is 24h; the mass concentrations of the DMF and methanol solutions used for centrifugal washing are 800g / L and 400g / L respectively; the temperature of the dried sample is 80℃, and the drying time is 8h.

[0048] (2) Preparation of Co / Cu-MOF-ZIF: Co / Cu-MOF is dispersed in a methanol solution and recorded as dispersion system A, and 2-methylimidazole (2-M) is dispersed in another methanol solution and recorded as solution B; then solution B is quickly poured into dispersion system A, and after dispersion system A and solution B are completely mixed, the mixed solution is subjected to ultrasound; then methanol and ethanol are used for redispersion and washing by centrifugation, and finally the centrifuged product is collected and dried to obtain the sample Co / Cu-MOF-ZIF. Among them, the mass concentration of the methanol solution is 400g / L; the weight ratio of Co / Cu-MOF and 2-M in the methanol solution is 1:4 respectively; the ultrasound duration is 20min in a beaker; the mass concentrations of the methanol and ethanol solutions used for centrifugal washing are 400g / L and 500g / L respectively; the temperature for drying the sample is 80℃, and the drying time is 10h.

[0049] (3) Preparation of Co / Cu-MOF-ZIF-LDH: Co / Cu-MOF-ZIF, nickel nitrate hexahydrate and ferric nitrate nonahydrate are dispersed in an ethanol solution and continuously stirred by magnetic stirring; then, anhydrous ethanol and deionized water are centrifuged for redispersion and washing, and finally, the final product, i.e., a novel flower-shaped composite flame retardant, is obtained by drying. The mass concentration of the ethanol solution is 500 g / L; the weight ratio of Co / Cu-MOF-ZIF, nickel nitrate hexahydrate and ferric nitrate nonahydrate in the ethanol solution is 20:8:1 respectively; the speed of the magnetic stirring is 500 rpm, and the stirring time is 6 h; the temperature condition of the freeze drying is -60 ° C, and the drying time is 11 h.

[0050] The Co / Cu-MOF-ZIF-LDH flame retardant prepared above is added to the polyurea B component to obtain a flame retardant polyurea composite material with excellent performance. The specific preparation method is: add the Co / Cu-MOF-ZIF-LDH flame retardant to a mixture of an amine chain extender and an amino-terminated polyether, ultrasonically and accompanied by stirring until uniform dispersion, and then add an isocyanate prepolymer to the mixture for reaction to obtain a polyurea material with excellent flame retardant properties. Wherein, the addition amount of the flame retardant is 6.0wt%. The weight ratio of the amine chain extender to the amino-terminated polyether is 1:5; the volume ratio of the isocyanate to the sum of the amine chain extender and the amino-terminated polyether is 1:1.1. Among them, the amino-terminated polyether is amino-terminated polypropylene glycol ether and amino-terminated polyglycerol ether; the amine chain extender is 3,3'-dichloro-4,4'diaminodiphenylmethane; the isocyanate is toluene diisocyanate (TDI), and the hydroxyl-terminated polyether is polybutylene glycol; the weight ratio of the isocyanate to the hydroxyl-terminated polyether is 5:4.

[0051] Example 4: Structural characterization of the flower-shaped composite flame retardant prepared in Examples 1-3

[0052] The Co / Cu-MOF, Co / Cu-MOF-ZIF and flower-shaped composite flame retardant prepared in Examples 1-3 were characterized by XRD, FT IR and SEM. The crystal structure of the flame retardant can be determined by XRD characterization, such as Figure 1 Through SEM analysis, the morphological changes of the products in each step can be obtained, such as Figure 2 The flower-shaped composite flame retardant prepared in Examples 1-3 was characterized by XPS. Figure 3 By performing XPS analysis on the flower-shaped composite flame retardant, its surface composition and the valence state of the elements can be obtained. Taking Example 1 as an example, a detailed description is as follows:

[0053] (1) XRD is used to test and characterize the crystal structure of the pre-prepared flame retardant, such as Figure 1 As shown in a, obvious characteristic peaks can be seen at 2θ = 10.16°, 12.14°, 17.12° and 24.82°, which correspond to the crystal planes (1 1 0), (0 20), and (1 3 1), thus confirming the successful synthesis of Cu-MOF. Figure 1 In b and 1c, the diffraction peaks attributed to Co-ZIF can be seen at 12.68°, 22.72°, and 24.45°, confirming the successful preparation of Co-ZIF.

[0054] (2) Figure 2 SEM images of samples prepared in each step. Figure 2 As can be seen from a, step (1) successfully synthesized a cubic Cu-MOF composed of a sheet-like structure containing cobalt elements, which has a relatively regular shape and a size of mostly 2-4 μm. The gaps between the layers of the sheet-like structure vary greatly. Figure 2 b It was found that after ultrasonic reaction in methanol solution, the cubic structure changed into a flower-like structure, and the petals were still 2μm layers with a relatively smooth surface. Figure 2 c shows that the overall flower structure has changed, some petals have gathered together, and the surface is no longer smooth. The number of petals has decreased, and the layers are thicker, and the central gathering is more obvious.

[0055] (3) Figure 3 a shows the full scan spectrum of XPS, from which we can see that the elements present in the sample are C, N, O, Cu, Co, Ni and Fe. At the same time, these are also the constituent elements of the composite material.

[0056] N 1s( Figure 3 b) shows a characteristic peak at 398.8 eV, which corresponds to the CN bond and may come from the ZIF in the composite material. Figure 3 The high-resolution image c) shows three characteristic peaks at 933.6, 941.9, and 953.6 eV, which belong to Cu 2p 3 / 2 、Cu 2p 3 / 2,sat and Cu 2p 1 / 2 The spin-orbit state of Cu in this composite material is confirmed to be in the +2 valence state. Figure 3 d is a high-resolution image of Ni 2p. It can be seen that there are four obvious characteristic peaks at 855.6, 861.2, 873.3 and 879.8 eV, of which 855.6 and 861.2 eV are Ni 2p 3 / 2 The spin-orbit peak and satellite peak of 873.3 and 879.8 eV are Ni 2p 1 / 2 The spin-orbit peak and satellite peak of confirm that the Ni element exists in the +2 valence state. Figure 3 The high-resolution image of Co 2p is shown in e. The peaks at 780.4 and 786.7 eV correspond to Co 2p 3 / 2 and its satellite peaks. The peaks at 795.6 and 802.6 eV correspond to Co 2p 1 / 2 and its satellite peaks, indicating that the Co element is in the +2 valence state in this composite material. Figure 3 f, 724.9 and 712.3 eV are respectively attributed to Fe 2p 1 / 2 and Fe2p 3 / 2, 717.9 and 731.2 eV belong to their satellite peaks, respectively, indicating that Fe exists with a valence of +3.

[0057] Example 5: Flame retardant performance test of the polyurea composite material prepared in Examples 1-3

[0058] In order to verify that the polyurea flame retardant composite materials prepared in Examples 1-3 have excellent flame retardant properties, a cone calorimeter was used for testing.

[0059] The specific method is: add the Co / Cu-MOF-ZIF-LDH flame retardant to the mixture of the amine chain extender and the amino-terminated polyether, mix them evenly by ultrasonic stirring, then mix them with the isocyanate prepolymer, and quickly transfer them to a 100*100*4mm 3 The standard test sample is obtained after curing in a cubic mold. Under the condition of 35kW radiation power, the sample mass and thickness are input, the sample is wrapped with aluminum foil, placed on the cushioning layer of the combustion box, pressed flat and evenly with the box cover, and then placed on the bracket of the weighing sensor for experiment to obtain the flame retardant performance of the material.

[0060] Through the above tests, it is found that the heat release rate (HRR) curve and the CO production rate (COP) curve of the polyurea composite materials prepared in Examples 1-3 have similar change trends. Now, the performance advantages of the prepared flame retardant polyurea composite material are analyzed by taking the HRR and COP of the flame retardant polyurea composite material of Example 3 as an example.

[0061] like Figure 4 As shown, the peak heat release rate (pHRR) of pure polyurea is 1341.30 kW / m 2 , while the pHRR of the flame retardant polyurea composite material prepared in Example 3 of the present application is 737.31 kW / m 2, a decrease of 45.03%. This is because, first of all, during the combustion process, the Cu, Co, Ni and Fe elements in the flame retardant can generate their corresponding oxides CuO, Co3O4, NiO and Fe2O3. It is these oxides that are dispersed in the flame-retardant polyurea composite material and exert their catalytic effect, so that the polymer matrix promotes the formation of a carbon layer during continuous combustion, thereby effectively blocking the generation and transfer of heat. While blocking the upper heat, it is also beneficial to prevent the continued combustion of the lower matrix. The formation of a dense carbon layer will naturally lead to a reduction in heat release. Secondly, the LDH in the Co / Cu-MOF-ZIF-LDH flame retardant will decompose into mixed metal oxides, CO2 and H2O during combustion. In this process, it will absorb a large amount of heat, thereby reducing the temperature of the polymer surface and the matrix. The released H2O will also play a positive role in reducing heat. In addition, the combustion of pure polyurea polymers will release toxic gases such as CO, which will cause great damage to the human body. According to Figure 5 From the CO release curve shown, it can be clearly seen that the CO release of the flame-retardant polyurea composite material prepared in the present application is much lower than that of pure polyurea as a whole. This is mainly due to the dense carbon layer blocking CO and harmful gases, reducing the amount of their overflow.

[0062] Example 6: Initial setting time and surface drying time of the flame retardant polyurea prepared in Examples 1-3

[0063] The initial setting time of the flame retardant polyurea prepared in Examples 1-3 was recorded: Under standard laboratory conditions (temperature (23±2)°C, relative humidity (50±10)%), different A and B components were mixed evenly according to a certain mass ratio and weighed 100g, poured into a 250mL beaker, and the mixture was quickly stirred and timed with a stopwatch. The time taken until the mixture no longer flows is the gel time. At the same time, the polyurea material without adding flame retardant was tested in the same way as a control. The results are shown in Table 1.

[0064] The surface drying time of the flame retardant polyurea prepared in Examples 1-3 was recorded: that is, under the same experimental conditions as above, the time when the stickiness disappears when the finger touches the surface is the surface drying time. At the same time, the polyurea material without adding flame retardant was tested in the same way as a control. The results are shown in Table 1.

[0065] Table 1. Gel time of polyurea materials and flame retardant polyurea prepared in Examples 1-3

[0066]

[0067] According to Table 1, the gel time of the flame retardant polyurea composite material prepared in Examples 1-3 of the present application is 77-101s, and the surface drying time is 347-451s. The gel time of the pure polyurea material used as a control is 75-96s, and the surface drying time is 340-439s. This shows that compared with the pure polyurea material, the gel time of the flame retardant polyurea composite material prepared in Examples 1-3 of the present application is only increased by 1-5s, and the surface drying time is only increased by 4-12s, which can be ignored and meets the requirements of rapid curing.

[0068] Example 7: Testing the mechanical properties of the polyurea composite material prepared in Examples 1-3

[0069] With reference to the test method provided in the "Test Method for Building Waterproof Coatings" (GB / T16777-2008), the tensile strength and tear strength of the material were tested. The specific method is: evenly apply the release agent on the surface of the sampling plate, and after the release agent is dried, prepare the flame-retardant polyurea composite material according to the ratio described in Examples 1-3, and remove it after curing at 25°C for 7 days. Use different cutters to cut the polyurea sheet into specimens for tensile strength test and tear strength test, measure the thickness of the polyurea sheet, input the data and set the tensile speed to 500mm / min, and perform tensile strength and tear strength tests respectively. At the same time, the polyurea material without adding flame retardant was used as a control for the same test. The results are shown in Table 2.

[0070] Table 2. Mechanical properties test results of polyurea and flame retardant polyurea prepared in Examples 1-3

[0071]

[0072] According to Table 2, the flame retardant polyurea composite material prepared in Examples 1-3 of the present application has a tensile strength of 18.49-19.68 MPa, a tear strength of 61.42-72.19 MPa, and an elongation at break of 302.52-319.01%. The pure polyurea material used as a control has a tensile strength of 20.35-21.49 MPa, a tear strength of 64.67-76.60 MPa, and an elongation at break of 312.45-332.69%. It can be seen that compared with pure polyurea, the flame retardant polyurea composite material prepared in Examples 1-3 has only a slight decrease in tensile strength, tear strength, and elongation at break. This shows that the novel flower-shaped composite flame retardant described in the present application has little effect on the mechanical properties of the polyurea material, and has produced unexpected technical effects compared with the prior art.

[0073] In summary, the novel flower-shaped composite flame retardant based on Co / Cu-MOF prepared by the method described in this application not only has good flame retardant properties, but also improves the flame retardant properties of polyurea materials without affecting the mechanical properties of polyurea materials, thus solving the problems existing in the prior art. At the same time, this application also provides an optimized polyurea formula, so that the polyurea material using the aforementioned flame retardant not only achieves a significant improvement in fire resistance, but also achieves rapid curing of the material, and has broad application prospects.

Claims

1. A novel flower-shaped composite flame retardant based on Co / Cu-MOF, characterized in that: Prepared by the following steps and methods: (1) Preparation of Co / Cu-MOF: Copper nitrate trihydrate, cobalt nitrate hexahydrate and 1,4-terephthalic acid are dispersed in a DMF solution, stirred magnetically until completely dissolved, and an acetonitrile solution is added and stirred continuously until the mixture is uniformly mixed; then the mixture is transferred to an autoclave for a solvothermal reaction, cooled to room temperature after the reaction is completed, centrifuged, washed and dried to obtain the product Co / Cu-MOF; (2) Preparation of Co / Cu-MOF-ZIF: The Co / Cu-MOF prepared in step (1) is dispersed in a methanol solution to obtain a dispersion system A, and 2-methylimidazole is dispersed in a methanol solution to obtain a solution B; the dispersion system A and the solution B are mixed and ultrasonically dispersed for 10 to 20 minutes; After centrifugal dispersion, washing and drying, the product Co / Cu-MOF-ZIF was obtained; (3) Preparation of Co / Cu-MOF-ZIF-LDH: The Co / Cu-MOF-ZIF prepared in step (2), nickel nitrate hexahydrate and ferric nitrate nonahydrate were dispersed in an ethanol solution and magnetically stirred for 5-6 hours; the final product Co / Cu-MOF-ZIF-LDH was obtained by centrifugal dispersion, washing and freeze drying.

2. The novel flower-shaped composite flame retardant based on Co / Cu-MOF according to claim 1, characterized in that: The weight ratio of copper nitrate trihydrate, cobalt nitrate hexahydrate and 1,4-terephthalic acid in step (1) is 1:(4-6):(8-10), and the specific conditions of the solvent thermal reaction are 110° C. to 130° C. for 12 to 24 hours; the volume ratio of the acetonitrile solution to the DMF solution is (0.7-1):

1.

3. The novel flower-shaped composite flame retardant based on Co / Cu-MOF according to claim 1, characterized in that: The weight ratio of Co / Cu-MOF to 2-methylimidazole in step (2) is 1:2 to 1:

4.

4. The novel flower-shaped composite flame retardant based on Co / Cu-MOF according to claim 1, characterized in that: The weight ratio of Co / Cu-MOF-ZIF, nickel nitrate hexahydrate and iron nitrate nonahydrate described in step (3) is (15-20):(6-8):

1.

5. The novel flower-shaped composite flame retardant based on Co / Cu-MOF according to any one of claims 1 to 4, characterized in that: The speed of the magnetic stirring in step (1) is 400-600 rpm, the stirring time is 20-30 min, and the drying condition is 60-80° C. for 6-8 h; the drying condition in step (2) is 60-80° C. for 8-10 h; the speed of the magnetic stirring in step (3) is 300-500 rpm, and the freeze-drying condition is -50--60° C. for 10-12 h.

6. The use of the novel flower-shaped composite flame retardant based on Co / Cu-MOF as claimed in any one of claims 1 to 5, characterized in that: The invention is used for preparing a polyurea material with excellent flame retardant properties. The specific method is as follows: adding a new flower-shaped composite flame retardant to a mixture of an amino-terminated polyether and an amine chain extender, and uniformly dispersing the mixture by ultrasonication; then adding an isocyanate prepolymer to the system for reaction, thereby obtaining a polyurea material with excellent flame retardant properties.

7. The use of the novel flower-shaped composite flame retardant according to claim 6, characterized in that: The addition amount of the novel flower-shaped composite flame retardant is 0.5-6.0wt%; the novel flower-shaped composite flame retardant is soaked in an acetone solution for 2-3 hours and then added into the mixture.

8. The use of the novel flower-shaped composite flame retardant according to claim 7, characterized in that: The weight ratio of the amino-terminated polyether to the amine chain extender is 3:1-5:1; the volume ratio of the isocyanate prepolymer to the sum of the amino-terminated polyether and the amine chain extender is 1:1-1:1.1; the isocyanate prepolymer is synthesized by prepolymerization of isocyanate and terminal hydroxyl polyether in a mass ratio of 5:4-5:8 under N2 atmosphere.

9. The use of the novel flower-shaped composite flame retardant according to claim 8, characterized in that: The isocyanate is 1,6-hexanediisocyanate (HDI), 2,2,4-trimethylhexanediisocyanate (TMHDI), isophorone diisocyanate (IPDI), tetramethyl meta-xylylene diisocyanate (TMXDI), toluene diisocyanate (TDI), dicyclohexylmethane diisocyanate (HMDI), 4,4'-diphenylmethane diisocyanate (4,4'-MDI) or 2,4'-diphenylmethane diisocyanate (2,4'-MDI); the amino-terminated polyether is polytetramethylene ether glycol di-p-aminobenzoate, amino-terminated polyoxypropylene ether, amino-terminated polyethylene glycol ether, amino-terminated polypropylene glycol ether, amino-terminated polyglycerol ether, amino-terminated pentaerythritol ether One or more; the amine chain extender is one or more of diethyltoluenediamine, dimethylthiotoluenediamine, 4,4'-bis-sec-butylaminodiphenylmethane, 2,4-diamino-3,5-dimethylthiochlorobenzene, 2,4-diamino-3-methylthio-5-propyltoluene, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, 4,4'-bis-sec-butylaminodicyclohexylmethane, 3,3'-dimethyl-4,4'-bis-sec-butylamino-dicyclohexylmethane, low molecular weight polyoxypropylenediamine, N,N'-dialkylmethyldiamine and 3,3'-dichloro-4,4'-diaminodiphenylmethane; the terminal hydroxyl polyether is one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol and polybutylene glycol.

10. Polyurea material with excellent flame retardant properties, characterized by: The polyurea material is prepared by the method in the application described in any one of claims 6 to 9, and the addition amount of the novel flower-shaped composite flame retardant in the polyurea material is 0.5 to 6.0 wt%.

Citation Information

Patent Citations

  • Halogen-free flame retardant and flame-retardant polyurea elastomer coating

    CN107916056A

  • Binary metal organic framework material applied to super capacitor and preparation method for binary metal organic framework material

    CN104992848A

  • Ultrathin layered material, and preparation method thereof

    CN105709614A

Cited By

  • Preparation method and application of an ultra-low addition amount MOF-derived LDH composite flame retardant

    CN119751977B

  • Novel hollow zigzag supramolecular flame retardant based on Cu-MOF as well as preparation and application of novel hollow zigzag supramolecular flame retardant

    CN120137193A